Bułgarskie przekłady trenów i fraszek Jana Kochanowskiego - Walczak-Mikołajczakowa, Mariola (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2024)
The type of poetry practiced by Jan Kochanowski is entirely foreign to Bulgarian literature, which until the mid-19th century was mainly devoted to religious writing and was not significantly influenced by Western literature. Nevertheless, the works of our Renaissance master are known in Bulgaria as they have been translated into Bulgarian since the 1980s. Jan Kochanowski's texts were translated by two outstanding translators: Ivan Valev and Panayot Karagyozov. The article includes an analysis of the translations by both translators – its aim is to indicate the translation strategies they use, and in the case of epigrams, also to compare the translated texts. The author discusses these translations, focusing mainly on the difficulties resulting from the systemic differences between Polish (inflectional language) and Bulgarian (analytical language, with a mobile dynamic accent). At the same time, an analysis of the creative skills of both Bulgarian translators proves that the differences in their readings of Kochanowski’s works, and thus a slightly different way of translating, result from their different personalities and interests.